Renal Sympathetic Denervation as Upstream Therapy During Atrial Fibrillation Ablation: Pilot HFIB Studies and Meta-Analysis - Turagam, Mohit K; Whang, William; Miller, Marc A; Neuzil, Petr; Aryana, Arash; Romanov, Alexander; Cuoco, Frank A; Mansour, Moussa; Lakkireddy, Dhanunjaya; Michaud, Gregory F; Dukkipati, Srinivas R; Cammack, Sam; et al. (JACC. Clinical electrophysiology, 2021)
OBJECTIVES: This study sought to determine the impact of adjunctive renal sympathetic denervation to catheter ablation in patients with atrial fibrillation (AF) and history of hypertension. BACKGROUND: There are limited data regarding the impact of upstream adjunctive renal sympathetic denervation (RSDN) to pulmonary vein isolation (PVI) in patients with symptomatic atrial fibrillation (AF) and hypertension. METHODS: The data for this study were obtained from 2 prospective randomized pilot studies, the HFIB (Adjunctive Renal Denervation to Modify Hypertension and Sympathetic tone as Upstream Therapy in the Treatment of Atrial Fibrillation)-1 (n = 30) and HFIB (Adjunctive Renal Denervation to Modify Hypertension and Sympathetic tone as Upstream Therapy in the Treatment of Atrial Fibrillation)-2 (n = 50) studies, and we performed a meta-analysis including all published studies comparing RSDN+PVI versus PVI alone up to January 25, 2020, in patients with AF and hypertension. RESULTS: At 24 months, AF recurrence occurred in 53% and 38% in the PVI and PVI+RSDN groups (p = 0.43) in the HFIB-1 study, respectively, and 27% and 25% in the PVI and PVI+RSDN groups (p = 0.80) in the HFIB-2 study, respectively. When combined in a meta-analysis including 6 studies (n = 725), adjunctive RSDN significantly decreased the risk of AF recurrence (risk ratio [RR]: 0.68; 95% confidence interval [CI]: 0.55 to 0.83; p = 0.0002; I2 = 0%) when compared with PVI. Six renal artery complications occurred in the HFIB-1 study and none occurred in the HFIB-2 study with RSDN. However, in the meta-analysis, there were no significant differences in overall complications between both groups (RR: 1.43; 95% CI: 0.63 to 3.22; p = 0.40; I2 = 7%). When compared with baseline, RDSN significantly reduced the systolic blood pressure (-12.1 mm Hg; 95% CI: -20.9 to -3.3 mm Hg; p < 0.007; I2 = 99%) and diastolic blood pressure (-5.60 mm Hg; 95% CI: -10.05 to -1.10 mm Hg; p = 0.01; I2 = 98%) on follow-up. CONCLUSIONS: The pilot HFIB-1 and HFIB-2 studies did not demonstrate a benefit with RSDN as an adjunctive upstream therapy during PVI. However, in the meta-analysis, adjunctive RSDN to PVI appears to be safe, and improves clinical outcomes in AF patients with a history of hypertension.
Keywords: Randomized Controlled Trials as Topic; Recurrence; catheter ablation; Atrial Fibrillation; výsledek terapie; pulmonary vein isolation; Catheter Ablation; lidé; Sympathectomy; Pilot Projects; recidiva; katetrizační ablace; atrial fibrillation; Treatment Outcome; pilotní projekty; prospektivní studie; sympatektomie; Prospective Studies; meta-analysis; randomizované kontrolované studie jako téma; fibrilace síní; hypertension; renal denervation; Humans